Superficial femoral artery stenting: Impact of stent design and overlapping on the local hemodynamics. (April 2022) - Colombo, Monika; Corti, Anna; Gallo, Diego; Colombo, Andrea; Antognoli, Giacomo; Bernini, Martina; McKenna, Ciara; Berceli, Scott; Vaughan, Ted; Migliavacca, Francesco; Chiastra, Claudio
Abstract: Background: Superficial femoral arteries (SFAs) treated with self-expanding stents are widely affected by in-stent restenosis (ISR), especially in case of long lesions and multiple overlapping devices. The altered hemodynamics provoked by the stent is considered as a promoting factor of ISR. In this context, this work aims to analyze the impact of stent design and stent overlapping on patient-specific SFA hemodynamics. Methods: Through a morphing technique, single or multiple stents were virtually implanted within two patient-specific, post-operative SFA models reconstructed from computed tomography. The stented domains were used to perform computational fluid dynamics simulations, quantifying wall shear stress (WSS) based descriptors including time-averaged WSS (TAWSS), oscillatory shear index (OSI), transverse WSS (transWSS), and WSS ratio (WSSRATIO ). Four stent designs (three laser-cut – EverFlex, Zilver and S.M.A.R.T. – and one prototype braided stent), and three typical clinical scenarios accounting for different order of stent implantation and overlapping length were compared. Results: The main hemodynamic differences were found between the two types of stent designs (i.e. laser-cut vs. braided stents). The braided stent presented lower median transWSS and higher median WSSRATIO than the laser-cut stents (p < 0.0001). The laser-cut stents presented comparable WSS-based descriptor values, except for the Zilver, exhibiting a median TAWSS ∼30% higher than the other stents. Stent overlapping provoked an abrupt alteration of the WSS-based descriptors. The overlapping length, rather than the order of stent implantation, highly and negatively impacted the hemodynamics. Conclusion: The proposed computational workflow compared different SFA stent designs and stent overlapping configurations, highlighting those providing the most favorable hemodynamic conditions. Highlights: Virtual stent implantation method based on mesh morphing. Hemodynamics simulations of stented, human superficial femoral artery models. The local hemodynamics induced by laser-cut vs. braided stents is different. In case of multiple stenting, the overlapping length highly impacts the hemodynamics. The order of stent implantation has a negligible impact on hemodynamics.